HUBUNGAN POLA ASUH DENGAN KEJADIAN KEKERASAN TERHADAP ANAK USIA SEKOLAH (6-18 TAHUN) DI KELURAHAN DUFA-DUFA KECAMATAN TERNATE UTARA - Fataruba, R; Purwatiningsih, S; Wardani, Y (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2009)
Background : Parents are the first and best teachers in the process of the human beings behavior, parenting if properly understood by parents so children grow and develop into a good figure but if the parents upbringing of children is wrong will impact on bad boy behavior. In the village Dufa-dufa Northern Distict of Ternate in North Maluku LPA survey Januari-Desember 2008 cases of child violence in the form violence physical (70 cases), sexual violence (3 cases), psychological violence (76 cases), economic exploitation/child labor (17 cases), sexual exploitation of children (1 cases), the child victims of conflict areas (15 cases), sexual abuse (4 cases), neglect of children (20 cases), murder (3 cases), the care and guardianship (12 cases). Purpose of this research is to determine whether there is a relationship parenting and violence against children at school age (6-18 years) in Dufa-dufa village Ternate northern districts.Methods: This study was a quantitative non experimental by using cross-sectional design in data collection, research using the questionnaire ad a data collection instrument, respondents in this study were parents who have children of school age, the number of 187 samples sample.Results: From the results of the statistic is obtained asymp sig number 0,000. Results of these tests showed P < ? (0,000 < 0,05) so that H0 is reject can in inflict that there was a significant association between parenting style and the incidents of violence against children, because the amount of views from C (coefficient contingency) is 28,8 percent for the contributed to variable parenting parents while the rest of the other variables not examined in this studyConclusion: There was a significant relationship between parenting style and the incidents of violence against children in Dufa-dufa village Ternate Northern districts. Keywords: Parenting, Genesis, Violence Against Children, School Age (6-18 Years).